Colour fringe detection and correction in YCbCr colour space. Issue 4 (1st June 2013) - Ju, Hae Jin; Park, Rae‐Hong
Abstract : Colour fringe is an artefact that mainly appears at the boundary of an object in an image, where colours change abruptly and luminance value is large. Thus, colour fringe should be corrected in a colour digital image. This study proposes a method for detection and correction of colour fringe in YC b C r colour space. The luminance value as well as gradient magnitudes/directions of YC b C r are used to detect colour fringed region. Then, chrominance values in colour fringed regions are corrected using those of pixels in the neighbouring regions along the colour fringe direction. The experimental results show the effectiveness of the proposed colour fringe detection and correction method.